Revisiting Acker’s gendered organizational theory: what women overcome to stay in the superintendency - Clark-Saboda, Jennifer L.; Lemke, Melinda (Frontiers in Education, 2023)
Despite key improvements to social, political, and economic status, women remain underrepresented in key leadership positions across the United States, including the superintendency. Feminist research underscores that androcentric systems maintain, valorize, and reproduce the experiences and knowledge claims of upper middle-class, heterosexual, white men. Documented in related fields, gender inequity within public school systems is thus in part, the result of bias, discrimination, and highly gendered organizational practices. Part of a larger qualitative descriptive study conducted in spring 2021 of the COVID-19 pandemic, the purpose of this research was to examine normative culture within the New York State (NYS) Board of Cooperative Educational Services (BOCES) superintendency, and how professional and personal supports affect women superintendents and ultimately their decision “to stay” in their position. The guiding research question for this part of the study asked how and why the NYS BOCES superintendency was gendered? Guided by and building upon Acker’s (1990) gendered organizational theory, 32 semi-structured, in-depth interviews were completed with NYS BOCES women superintendents. The BOCES organization was purposefully selected, in contrast to one of the 731 NYS public school districts, because of the level of political and economic power that BOCES superintendents have at the state level – and to that end, the role of women leadership in a highly influential state educational organization. Overall, study results are consistent with Acker’s research, finding that the NYS BOCES is a highly gendered organization, and also in specific ways tied to contemporary context. Chief among these included that women superintendents face countless gender inequities and barriers associated with staying in their leadership role, but professional legacy, the extent to which the work benefited families, and appropriate work-life balance were motivating factors. Concluding with implications for research and practice, study findings are significant because this study is the first to empirically examine the NYS BOCES and the career trajectories of its women superintendents – and to do so from a feminist epistemological perspective and gendered theoretical framework focused creating transformative change within research and practice.